Characteristics and equation of accounting vocational theory trial test items for vocational high schools by subject-matter teachers’ forum - Purnama, Dian Normalitasari (REID (Research and Evaluation in Education), 2018)
This study is aimed at: (1) understanding the characteristics of Accounting Vocational Theory trial test items using the Item Response Theory and (2) determining the horizontal equation of Accounting Vocational Theory trial exam instruments. This was explorative-descriptive research, observing the subject of the eleventh-grade students. The research objects were test instruments and responses of students from six schools selected through the stratified random sampling technique. The data analysis employed review sheets and BILOG program for the Item Response Theory 2PL. The findings were as follows. (1) The test item review of test packages A and B found 37 good quality items, the Item Response Theory using 2PL showed that Package A Test generated 27 good questions, Package B Test contained 24 good questions. (2) The question equating using the Mean/Sigma method resulted in the equation of = 1.168bx + 0.270, with the Mean/Mean method resulting in the equation of = 0.997bx - 0.250, the Mean/Mean method at 0.250, while Mean/Sigma method at 0.320.